2006
DOI: 10.1200/jco.2005.03.6830
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CD4+CD25+ Regulatory T Cells in Patients Treated With High-Dose Interleukin-2 for Metastatic Melanoma or Renal Cell Carcinoma

Abstract: The number of Tregs, defined as CD4+CD25(hi) T cells is increased in patients with MM and RCC. High-dose IL-2 resulted in a significant decrease of Tregs in those patients achieving an objective clinical response to IL-2 therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
192
5

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(209 citation statements)
references
References 39 publications
12
192
5
Order By: Relevance
“…In RCC and melanoma, a correlation between decreasing numbers of Tregs and response to IL-2 therapy was described previously. 37 In our trial, induction of antigen-specific IL-10 secretion in patients may not only be explained by a TH2-polarization of the immune response. Alternatively, IL-10 release could also be the consequence of immunosuppressive networks induced by the vaccine, in particular Tregs.…”
Section: Discussionmentioning
confidence: 58%
“…In RCC and melanoma, a correlation between decreasing numbers of Tregs and response to IL-2 therapy was described previously. 37 In our trial, induction of antigen-specific IL-10 secretion in patients may not only be explained by a TH2-polarization of the immune response. Alternatively, IL-10 release could also be the consequence of immunosuppressive networks induced by the vaccine, in particular Tregs.…”
Section: Discussionmentioning
confidence: 58%
“…This observation suggests that a subset of tumor-infiltrating CD4 ϩ T cells may impede antitumor T and NK cell function (10). This inhibitory T cell subset may include CD4 ϩ CD25 ϩ Foxp3 ϩ T cells (referred to as regulatory T (Treg) 3 cells) capable of significantly inhibiting T cell immunity (11,12). In support of this scenario are studies reporting that in vivo depletion of CD4 ϩ T cells is moderately effective in raising immunity against established tumors.…”
Section: Targeting Molecular and Cellular Inhibitory Mechanisms For Imentioning
confidence: 51%
“…We are uncertain why some but not all patient Vg9Vd2 T cells respond to in vitro culture but we speculate one reason of poor proliferation of Vg9Vd2 T cells is the effect of regulatory T cells (Treg). A previous study showed that the percentage of Treg was high in circulating blood of malignant melanoma patients 55 and suggested that Treg have a negative effect upon Vg9Vd2 T cell proliferation in vitro. 56 We are continuing to investigate this issue.…”
Section: Discussionmentioning
confidence: 99%